طائفة الزيلوت اليهودية من نشاتها الى سقوطها 6ق.م-70م - بن تامر مريم (جامعة الوادي University of eloued, 2018)
تهدف الدراسة إلى توضيح الجذور التاريخية لطائفة الزيلوت اليهودية, وذلك من خلال العودة إلى المكابيين وثورتهم التي تعتبر ذات صلة تاريخية بالزيلوت, إذ برزوا لنفس الأسباب والدوافع الرافضة للخضوع والهيمنة. كذلك بينا من خلال هذه الدراسة سياسات الولاة الرومان واليهود المتعاونين معهم, وبينا كيف أن الساحة الدينية والسياسية في تلك الحقبة لم تكن خالية للزيلوت وحدهم, بل كانت هناك عدة طوائف متباينة في أفكارها ومواقفها من السلطة الرومانية بيم مؤيد ومعارض. بينت هذه الدراسة الأسباب والدوافع التي تؤدي إلى العنف والتطرف, ومن ثم قيام الثورة الرومانية, والتي بالرغم من اعتزاز اليهود بها إلا أنها قد شيبت بمعكرات أضعفت نتائجها, إذ أن اليهود لم يندمجوا فيها جميعا بل كان كثيرا منهم يكيدون لها ولرجالها في مختلف المناسبات, إضافة إلى الخلافات التي كانت تنشا بين رجال حركة الزيلوت أنفسهم, والتي أدت إلى تحول الحرب اليهودية الرومانية إلى حرب أهلية طائفية, ومن ثم تسببوا بحماقاتهم في الكارثة التاريخية الماحقة التي انزلها القائد تيتوس باليهود, فهدم الهيكل وخرب القدس وأباد الشعب, ثم فقدان اليهود بعد ذلك لوجودهم ودورهم التاريخي بان بدا عصر الشتات الأكبر في تاريخهم. The study aims at clarifying the historical roots of the Jewish zealot community, by returning to the Maccabees and their revolution, which are historically related to the Zilot, as they emerged for the same reasons and motives that reject submission and hegemony. The study also examined the policies of the Roman governors and their Jewish collaborators, and showed how the religious and political arena of the period was not free of the Zilot alone. There were several different sects in their ideas and attitudes from the Roman authorities, with their support and opposition. This study shows the reasons and motives that lead to violence and extremism, and then the Roman revolution, which despite the pride of the Jews, but it has been distorted by the effects of the weak, as the Jews did not merge all of them, but many of them Vkidon for her and men on various occasions, To the differences that arose between the men of the Zilot themselves, which led to the transformation of the Roman Jewish war into a sectarian civil war, and then caused their foolishness in the historical disaster of the tithe brought down by the leader Titus Jews, destroyed the Temple and the destruction of Jerusalem and destroyed the people, and then the loss of Jews after their existence And its role M historical that seemed the era of the largest diaspora in their history.
مذكرة ماستر تاريخ تخصص تاريخ الحضارات القديمة
Keywords: طائفة الزيلوت اليهودية -الحرب اليهودية الرومانية 66م-70م - يهوذا الجليلي; La communauté juive de Zilot - Dieu dans le public 66 m - 70 m - Judean Galilean; The Jewish Zilot Community - The Roman Jewish War 66 - 70 CE - Judean Judaea